An Efficient Unstructured P2P Overlay over MANET Using Underlying Proactive Routing - Shah, N.; Depei Qian (2011 Seventh International Conference on Mobile Ad-hoc and Sensor Networks, 2011)
In a traditional unstructured P2P file sharing network, each peer randomly establishes connection with certain number of other peers to ensure the connectivity of the P2P overlay. This random overly leads to redundant traffic and P2P network partition in mobile ad hoc network (MANET). This paper explains the construction of an efficient unstructured P2P overlay over MANET (E-UnP2P) using a proactive underlying routing protocol. Instead of having redundant links among the peers in the P2P network, E-UnP2P introduces a root-peer connecting all peers. Each peer maintains connection with closest peers such that it can reach the root-peer. A peer constructs a minimum-spanning tree consisting of itself, its directly connected neighbor peers and 2-hop away neighbor peers to identify far away peers and builds the overlay closer to the physical network. We can show by simulation that E-UnP2P performs better in comparison with the existing approach (XL-Gnutella).